Clinical manifestations, laboratory findings, and imaging in COVID-19 - Goutam Goswami; Nikhil Vinayak; Maneesh Kumar; Pradeep Kumar Sharma (Wolters Kluwer Medknow Publications, 2020)
Coronavirus disease 2019 (COVID 19) caused by severe acute corona virus 2 (SARS-CoV2) strain is an ongoing pandemic affecting more than 200 countries worldwide. On April 15, 2020 total 2,000,995 persons are affected with 126,783 deaths worldwide. It is mainly an adult disease, but it can affect any age group. Children are less likely to be affected and severity and mortality is less compared to adults. Infants however are more prone to develop severe disease. The disease has human to human transmission with an incubation period of 2-14 days. It spread through respiratory droplets which enter the body through respiratory tract or conjunctiva. Children usually present with fever, cough, and breathing difficulty. Diarrhea and abdominal pain can also be seen. Pulmonary and extrapulmonary complications can occur, but these are less frequent in children except infants. Critical illness and mortality increase significantly with age and associated comorbidities. In children, no typical laboratory findings are seen. Radiological investigations are not specific and hence their routine use is not recommended especially in milder cases. Subpleural lesion with ground glass opacification is the most common radiological finding. Confirmation is done by real-time reverse transcriptase polymerase chain reaction. The management is mainly supportive. Drugs and vaccines are under trial. Prevention is done by breaking the chain of transmission.